Patterned-ground facilitates shrub expansion in Low Arctic tundra - Frost, Gerald V; Epstein, Howard E; Walker, Donald A; Matyshak, Georgiy; Ermokhina, Ksenia (Environmental research letters, 2013)
Recent expansion of tall shrubs in Low Arctic tundra is widely seen as a response to climate warming, but shrubification is not occurring as a simple function of regional climate trends. We show that establishment of tall alder (Alnus) is strongly facilitated by small, widely distributed cryogenic disturbances associated with patterned-ground landscapes. We identified expanding and newly established shrub stands at two northwest Siberian sites and observed that virtually all new shrubs occurred on bare microsites ('circles') that were disturbed by frost-heave. Frost-heave associated with circles is a widespread, annual phenomenon that maintains mosaics of mineral seedbeds with warm soils and few competitors that are immediately available to shrubs during favorable climatic periods. Circle facilitation of alder recruitment also plausibly explains the development of shrublands in which alders are regularly spaced. We conclude that alder abundance and extent have increased rapidly in the northwest Siberian Low Arctic since at least the mid-20th century, despite a lack of summer warming in recent decades. Our results are consistent with findings in the North American Arctic which emphasize that the responsiveness of Low Arctic landscapes to climate change is largely determined by the frequency and extent of disturbance processes that create mineral-rich seedbeds favorable for tall shrub recruitment. Northwest Siberia has high potential for continued expansion of tall shrubs and concomitant changes to ecosystem function, due to the widespread distribution of patterned-ground landscapes.